Festo, schmesto! [patent law and the doctrine of equivalents]. - Frank, S.J.
Does a recent US Supreme Court decision in the case of Festo Corp. versus Shoketsu Kinzoku Kogyo Kabushiki Co., Ltd., expand or limit the rights of patent holders to sue copycats? This article discusses the "doctrine of equivalents," which allows the patent holder to expand a patent beyond its literal terms to cover subject matter it doesn't expressly mention. At its heart are two premises: first, it is difficult to capture the full scope of technical innovation in words; and second, some people are wiseguys. No matter how carefully a patent claim is worded, no matter how well it appears to cover an invention, there will always be those who will search eagerly for the loophole, a way to circumvent language and avoid infringement. Patent law rewards innovation with exclusivity for a limited time period. But the reason patents are printed and published is to encourage still further innovation. The problem arises when someone slyly avoids a patent's language without contributing anything new-in effect, appropriating the benefits of an invention without enriching the art. Ultimately, the doctrine of equivalents plays a marginal role in patent law. That's because reasonably well-written patent claims are not, in the main, easy to avoid if the benefits of the invention are to be retained. Courts apply the doctrine to catch the occasional wiseguy while defending the certainty patent claims are supposed to provide. The Supreme Courts latest adjustment notwithstanding, that role is likely to continue
Keywords: Festo Corporation; Shoketsu Kinzoku Kogyo Kabushiki Company; Doctrine of equivalents; Loophole; Patent claim; Patent holders rights; Patent law; Technical innovation